Evaluation of anti-tyrosinase, anti-collagenase, and in vitro sun protection factor (SPF) of Ajwa date fruit (Phoenix dactylifera L.) - Ramli, Nur Asyiqin; Gani, Siti Salwa Abd; Halmi, Mohd Izuan Effendi; Zaidan, Uswatun Hasanah (Universiti Putra Malaysia Press, 2024)
This research explores the potential of Ajwa date fruit extract as a bioactive component in cosmeceutical formulations, with particular emphasis on its anti-tyrosinase, anti-collagenase, and ultraviolet (UV) protection capabilities. The antioxidant activity was determined using the design of response surface methodology, considering the factor of sample-to-water-as-solvent ratio, extraction time, and size of the sample. This factor possesses the capacity to exert an influence on the production of antioxidants and enhance the efficacy of the extraction procedure. The Ajwa date fruit extract was obtained using the Soxhlet method. The extract showed notable inhibition percentages of 67.77 and 49.12 for anti-tyrosinase and anti-collagenase activities, respectively. Additionally, it revealed a sun protection factor value of 17.09. Previous research has indicated that Ajwa dates exhibit significant inhibitory properties against tyrosinase and collagenase enzymes, making them potentially valuable in cosmetic applications. Therefore, research has demonstrated this study’s promise in skin pigmentation, elasticity, and UV protection. The study places significant importance on exploring natural alternatives in cosmetics. It highlights the encouraging outcomes obtained from using Ajwa date fruit extract, emphasising its potential for future advancements in cosmeceuticals. The present study offers a valuable opportunity to produce skincare formulas that are both safer and more effective.